(untitled) (PerCursos, 2021)
This article is result of the experience of their authors with the psychoanalytic clinic and the theater. As an objective, we aim to articulate the concept of theatricality (Josette Féral) with Antonin Artaud’s theater of cruelty, and then develop an analysis of theatricality experienced in the subject’s subjective life dimension daily. Artaud’s criticism of the ways of doing theater in his time makes us question what is the art or artistic activity that interest us and how it presents itself in our daily lives, addressing cases known to the general public: Joker (2019) from the film with the same name and two real cases, Sandro, of the 174 bus in 2002, and William, who stopped the Rio-Niterói bridge in 2019. With their stories we rescued the reception by listening - which goes far beyond listening - as an essential tool for someone to become a subject. We conclude that theatricality can be an outlet found in daily life, by ordinary citizens, to subvert the Other’s discourse, which throws them to the challenge of surviving the violence inherent to suburban life, racism, poverty, physical and speech violence. We believe that, perhaps, by transforming submission into oppression, these real-life characters have at least a moment to change their stories.